MAKNA KERJA BAGI PENGUSAHA KECIL MUSLIM DI TENGAH PERKEMBANGAN BISNIS KULINER - Muhammad Djakfar (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2015)
The emergence of small business enterprises has shown an inevitability to support economic power in a country, even in Indonesia. There are so many labors that are included in this small business enterprise so that their existence becomes stabilizer and dynamic maker, either in a stable or emergency condition of the country’s economy. This research is trying to understand the meaning of working to Moslem’s small business enterprises and to know their motives in developing their business and also their marketing management and their human resource construction that they have done. This research uses qualitative approach, phenomenology for exact. While the data taken from deep interview, participant observation, and documentation. The result shows that the motives of developing their business is because of spiritual factor and also hobby. The marketing strategy is done through advertising, joining the scientific forum, and opening new branches. The employees’ construction is done humanely and with good attitude, while the meaning of “working” to the workers is as a means of worship, economy, relationship, education, and da’wah.Copyright (c) 2016 by Al-Ihkam. All right reservedDOI: 10.19105/al-ihkam.v10i2.736